MENINJAU KEMBALI PENYELESAIAN SENGKETA KONSUMEN DI INDONESIA : ASPEK KELEMBAGAAN DALAM RANGKA TERCAPAINYA KEPASTIAN HUKUM - Afriana, Anita; Sudaryat, Sudaryat; Mantili, Rai; Rahmawati, Ema (Institut Hindu Dharma Negeri Denpasar, 2019)
Due to the upward trends of business transaction both in conventional and online basis, it is deemed necessary to find an effective ways to settle disputes in the event of a losses to the consumers.In general, consumer disputesinvolve small amount of lossand complaint filed by the consumers for material compensation. In Indonesia, consumer disputeresolutionis carried out not only by the Consumer Dispute SettlementBody (BPSK)but also throughthecourts. Recently,there are manynewly-established consumer disputesettlement institutions.A quick, simple,and low-cost consumer dispute mechanism isneeded to cope with Indonesian economic growth by accelerating the time of a dispute settlement (time efficiency). The purpose of this research is find out how consumer disputes are resolved in Indonesia and legal discource in the frame work oft he consumer?s disputere solution which have lawcertainty.it can be concluded that the pluralityof consumer disputesettlement in Indonesia has ledtoconvoluted mechanisms and procedures in settling disputes. Dispute settlement through Badan Penyelesaian Sengketa Konsumen/Consumers Dispute Settlement Agency (BPSK) is not final and binding. Through this article, it is recommendedto utilise Small Claims Procedures that combines informal and formal mechanisms in order to achieve legal certainty in the settlement of consumer disputes in Indonesia.